Faktor Dominan Bahasa Indonesia dan Peranan Orang Tua dalam Perkembangan Bahasa Banjar Anak Usia 4 Tahun - Nadia Ruhama Salsabilah; Nur Aisyah; Norlatifah Hasanah; Siti Mutiah (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to identify the dominant factor of the use of Indonesian rather than their own regional language and the role of parents in the language development of 4-year-old children. The increasing use of gadgets among all ages has had many influences on children, one of the 4-year-old children who has been studied, named Mufidah, tends to use Indonesian rather than Banjarese, this is a factor in the use of gadgets given by her parents. This study uses a qualitative approach, a research method that focuses on in-depth observation to understand a phenomenon or social symptom. The techniques used in data collection are by analyzing various sources, recording, and interviews. The results of the study show that although the use of Indonesian is more dominant than Banjarese, the role of parents must be active in minimizing the use of gadgets for children by limiting time and also supervising the selection of videos watched. With the active role of parents, it will certainly have a positive impact on children in the use of gadgets and vice versa if parents do not supervise their children when they use gadgets, it will have a negative impact on children.